APPROACH FOR URBAN TERRITORY PLANNING BASED BIG DATA - BRADJI, LOUARDI; TABET, KHAOULA; LAOUAR, MOHAMED RIDDA (Courrier du Savoir; Vol 22 (2017): COURRIER DU SAVOIR (JANVIER), 2017)
Over the last few years, urban data has become more complex for the reason that large amount of data are being available lately, along with the rapid change of technologies and mobile applications and new problems have discovered. Therefore, urban territory planning organizations have believed that urban data analytics tools are really important subject in order to manage a large amount of complex data, which can lead to improve urban territory planning and help urban practice to reach a high level of efficiency and work flow accuracy, if these data analytics tools applied correctly, but the questions are how urban organizations are applying these tools today, and how to think about it‟s future use? This paper gives a response to this question by proposing an approach that combines big data technologies such as NoSQL systems ,Hadoop and MapReduce. We have used current technologies to implement and validate the proposed approach which offers the ability to handle large data to achieve better decision in urban territory planning domain.